Strengthening the Values of Religious Moderation in Early Childhood Education Through the Implementation of the Independent Curriculum: Penguatan Nilai-Nilai Moderasi Beragama Pada Pendidikan Anak Usia Dini Melalui Implementasi Kurikulum Merdeka - Hidayati, Zuhriyyah; Zaini, Nur; Sya’roni, Muhammad (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Religious moderation has become an important issue recently in line with the increasing conflict originating from ideological and identity political competition, which tends to be extreme, both right and left. In an effort to minimize the occurrence of conflict due to these problems, the Ministry of Religion Affair has launched religious moderation as the main program in developing Indonesia. The strategy of internalizing the values ​​of religious moderation can be carried out by all levels of society, one of which is early childhood education institutions. The strategy is to use the ABCD approach where the focus of this service is more directed at implementing the Kurikulum Merdeka, namely the activities of the Proyek Penguatan Profil Pelajar Pancasila with the theme We are All Brothers. The results of this service are that partners can develop P5 teaching modules according to the guidelines, receive material regarding strategies for internalizing the values ​​of religious moderation in PAUD, visit Pancasila villages, and receive a literacy corner and religious moderation APE. The level of partner satisfaction is also quite good so there is a commitment to continue carrying out activities to internalize these values ​​in the following years